Penerapan Model Jigsaw Berbantuan Multimedia untuk Meningkatkan Hasil Belajar Bangun Datar Peserta Didik Kelas IVSekolah Dasar - Annisa, Lusi; Desyandri, Desyandri (Universitas Negeri Padang, 2025)
This research aims to describe the application of the Jigsaw-type cooperative learning model assisted by multimedia in improving mathematics learning outcomes in-plane material in class IVa at SDN 19 Kampung Baru. The research uses two types of approaches, namely a qualitative approach and a quantitative approach. The subjects were 25 class VIa students in the January-June semester of the 2023/2024 academic year. The research results showed that the teaching module assessment in Cycle I, Meeting 1, was 86%, Cycle 1, Meeting 2, was 89%, and the average from Cycle 1 was 88%. Then in cycle II 95%. Teacher aspect assessment in cycle I, meeting 1, 84%, cycle 1, meeting 2, 88.4%, average in cycle 1, 86%. Then in cycle II, it was 95.4%. Assessment of student aspects in Cycle I, Meeting 1, 84%, Cycle 1, Meeting II, 86.3%, average for cycle I, 85%. Then in cycle II 95%. Student learning outcomes for cycle I, meeting 1, 78%, cycle 1, meeting II, 82%, average for cycle 1 79.8 and cycle II 87. In conclusion, the Jigsaw-type cooperative model can improve student learning outcomes in mathematics learning on plane material in class VIA SD Negeri 19 Kampung Baru.